Location decision-making processes of internationalising firms: a multiple case study investigation - Al Qur'an, Marwan (Curtin University, 2005)
Research into the location decision of Australian international firms was primarily directed toward investigating motivations of Australian investors for setting up their foreign direct investments (FDI) in specific foreign countries. Nevertheless, the strategic decision-making process concerning the selection of a beneficial foreign country for either Australian or Western Australian international operations has been neglected in the existing literature; hence, an evident and significant gap was identified. Therefore, the current exploratory investigation used an interpretive paradigm to examine ‘how do Western Australian internationalising firms arrive at a beneficial foreign location choice for their international operations and hence attain successful international expansion. As an attempt to provide rich and deep insights into managerial actions and procedures, as well as critical success factors, that should be considered in effective international location decision-making process to attain a beneficial foreign location choice, five empirical comparative in-depth case studies excluding a pilot case study were purposefully selected from among sixteen potential Western Australian firms which established manufacturing and service operations abroad. Furthermore, seven international location decision-making processes were examined within these five cases through relying on several data sources: in-depth face to face interviews, short telephone and follow-up interviews and questionnaire instrument as primary data sources besides field notes, documents review when available and internet sources as secondary data sources. Two main stages of analysis were undertaken in the current research, namely, within and cross-case analyses.The empirical findings of the extant research show that a thorough consultative and international experience-based strategic decision process should be considered to attain effective foreign country selection decisions. The consultative decision process encompasses five crucial managerial phases; that is, (1) strategic analysis of internationalisation drivers, (2) strategic searching and development of location factors and alternatives, (3) acquiring of adequate and relevant information about the prospective locations and, hence, strategic assessment for these alternatives, (4) strategic selection of final beneficial foreign location choice, and finally, (5) effective implementation of the selected location choice. Results reveal that the decision process cannot separately lead to the selection of a beneficial foreign location choice in the absence of four critical success factors, i.e., (1) international business experience of the selected location team, (2) the country knowledge about the potential foreign locations, (3) in-house and external consultations with international business experts and (4) identification of a trustworthy and internationally experienced manager or local partner for the international operation. The findings also illustrate that the comprehensive foreign country selection decision process is a multi-stage decision process which incorporates three separate location selection processes, namely, (1) country selection, (2) city selection and (3) site selection process. The current research extends the satisficing or bounded rational decision theory by confirming the appropriateness and the effectiveness of the theory in foreign country selection decisions.In addition, the earlier critical success factors are adding new and important aspects of knowledge to the existing research on location decision-making process in international business, as well as foreign direct investment decisions. Accordingly, the former management phases and critical success factors were integrated into a conceptual model. The major and the unique contribution of the current thesis to existing theory is the development of a decision model which combines two fields of management research; that is, strategic decision-making and location decision-making in international business. The research provides important methodological contributions to international business research in relation to an effective multiple case study approach to capture elements of the comprehensive and complex international location decision-making process. Finally, the research findings and decision model have practical managerial implications for both international and internationalising firms by assisting them to improve the effectiveness of their foreign country selection decision processes. Further, the findings provide benefits for foreign investment policy-makers as well as local development officials in both home and host countries by assisting them to increase their outward FDI and attract more inward FDI and, consequently, boost the economic development movement in their countries.